Effect of cyclicity and Equine Chorionic Gonadotropin (eCG) in fixed-time artificial insemination programs in Bos indicus cattle - Salgado, Roger D; Maza, Libardo A; Vergara, Oscar D (Revista Colombiana de Ciencias Pecuarias, 2013)
Summary Background: fixed-time artificial insemination programs (FTAI) in Bos indicus heifers have low pregnancy rates. Objective: the aim of this study was to evaluate the effect of cyclicity and equine chorionic gonadotropin (eCG) treatment in fixed-time artificial insemination (FTAI) programs in Bos indicus cattle. Methods: a total of 100 heifers were assigned to four treatments using a completely randomized design with a 2 x 2 factorial arrangement, where one of the factors was ovarian status (cyclic or acyclic) and the other was eCG use (with and without eCG). Follicular growth, ovulation, and pregnancy rates were evaluated using analysis of variance or X2 test. Results: no effect (p > 0.05) of cyclicity on follicular diameter was observed while eCG showed a significant effect (p < 0.05). Cyclicity status and eCG use had no significant effect (p > 0.05) on ovulation or pregnancy rates. Conclusions: the eCG application at the time of intravaginal device (IVD) withdrawal increased the size of the ovulatory follicle on insemination day. However, the ovarian state and the use of eCG did not affect ovulation and pregnancy rates of the heifers. Key words: follicular growth, heifers, ovulation, pregnancy~ Resumen Antecedentes: los programas de inseminación artificial a tiempo fijo en novillas Bos indicus presentan bajas tasas de preñez. Objetivo: el objetivo de esta investigación fue evaluar el efecto de la ciclicidad y de la hormona gonadotropina coriónica equina (eCG) en programas de inseminación artificial a tiempo fijo (IATF) en ganado Bos indicus. Métodos: se utilizaron 100 novillas y se conformaron cuatro tratamientos utilizando un diseño completamente aleatorizado, con arreglo factorial 2 x 2 con dos categorías, según el estado ovárico (cíclicas y acíclicas) y la utilización de eCG (con y sin eCG). El crecimiento folicular, tasas de ovulación y de preñez se analizaron a través de análisis de varianza. Resultados: no se presentó efecto significativo (p > 0,05) de la ciclicidad sobre el diámetro folicular; mientras que la eCG sí presentó efecto significativo (p < 0,05). La ciclicidad y la aplicación de eCG no tuvieron efecto significativo (p > 0,05) sobre las tasas de ovulación y de preñez. Conclusiones: la aplicación de eCG al momento de retirar el dispositivo intravaginal (DIV), aumentó el tamaño del folículo ovulatorio el día de la inseminación; sin embargo, el estado ovárico y el uso de eCG no afectaron las tasas de ovulación y de preñez en las novillas del presente estudio. Palabras clave: crecimiento folicular, novillas, ovulación, preñez~ Resumo Antecedentes: os programas de inseminacao artificial em tempo fixo feitos em novilhas Bos indicus apresentam baixa taxa de prenhez. Objetivo: o objetivo desta pesquisa foi avaliar o efeito da ciclicidade e da gonadotrofina coriónica equina (eCG) em programas de inseminacao artificial em tempo fixo (IATF) em gado Bos indicus. Métodos: utilizaram-se 100 novilhas divididas em quatro tratamentos utilizando um delineamento inteiramente casualizado com arranjo fatorial 2 x 2 com duas categorias de acordo como o status ovariano (cíclico e acíclico) e o uso de eCG (com e sem eCG). O crescimento folicular, a taxa de ovulacao e a taxa de prenhez analizaram-se usando análise de variáncia. Resultados: nao houve efeito significativo (p > 0,05) da ciclicidade sobre o diámetro folicular, en quanto que a eCG apresentou efeito significativo (p < 0,05). A ciclicidade e a aplicacao de eCG nao tiveram efeito significativo (p > 0,05) sobre a taxas de ovulacao e prenhez. Conclusoes: a aplicacao de eCG no momento da remocao do dispositivo intravaginal (DIV), aumentou o tamanho do folículo ovulatório no dia da inseminacao, embora, o status do ovário e o uso de eCG nao afetaram as taxas de ovulacao e prenhez nas novilhas avaliadas nesta pesquisa. Palavras chave: crescimento folicular, novilhas, ovulaqáo, prenhez~